Performance analysis of evacuated tube collector based solar heat for industrial process (SHIP) system in Malaysian climate - Akbar, Muhammad Ali; Rashid, Muhammad Mahbubur; Embong, Abd Halim; Haja Mohideen, Ahmad Jazlan; Akhter, Muhammad Naveed (Taylor’s University, 2022)
Industries commonly use natural gas boilers to fulfil the hot water and steam requirement of the factories. However, the emission of greenhouse gasses increases in the environment due to the vast usage of natural gas boilers. Therefore, Solar Heat for Industrial Process systems is being introduced around the globe to supply hot water and steam in the processing activities of factories. The performance and viability of Solar Heat for Industrial Process systems depend on several variables such as heating capacity, piping circuit, solar irradiation, cost of the project, shading effect, and storage method. This research aims to evaluate, analyse, and validate the Solar Heat for Industrial Process system performance and potential of greenhouse gas reduction. The performance analysis of the recently installed Solar Heat for Industrial Process system was carried out successfully for three months (October-December 2020) based on different analysis parameters. The monthly analysis shows that the Evacuated Tube Collectors produced 50.03%, 49.46%, 47.10% efficiency, and system efficiency recorded as 45.77%, 46.65%, 45.23%. The average losses rate per month is 2.98%. This rate met the requirement for final energy delivery terms to storage tank procedure. The Solar Heat for Industrial Process system also reduces a significant Carbon Dioxide emission with 20.7 Tons over the analysis period. This paper presents solar thermal performance analysis, particularly system efficiency and greenhouse gasses reduction. Results are highly acceptable and show the viability of Solar Heat for Industrial Process system in Malaysia climate is proven.